Student midwives' satisfaction with enquiry-based learning. - Tully SL (British Journal of Midwifery, 2010)
Studies have evaluated enquiry-based learning (EBL) and problem-based learning in terms of student learning (Connelly and Seneque, 1999; Yeung et al, 2003; Williams, 2004), but the aim of this study was to listen to student midwives' experiences of EBL and evaluate their satisfaction with EBL as a teaching and learning strategy. The study took a qualitative phenomenological research approach. Analysis of the data identified five themes: students' satisfaction with EBL; impact on clinical learning; students' motivation; issues around group work; and the role of the facilitator. These themes are discussed in detail in this article with relation to available published literature. Overall, the students enjoyed and valued EBL as a learning strategy. A number of issues were identified and this article makes various recommendations to inform future developments in midwifery education.